Crataegus monogyna buds and fruits phenolic extracts: growth inhibitory activity on human tumor cell lines and chemical characterization by HPLC–DAD–ESI/MS - Rodrigues, Sandra (2012)
Crataegus monogyna has been extensively studied due to its various alleged health benefits. This study aimed to determine the human tumor cells growth inhibitory activity of phenolic extracts of its flower buds and fruits in three phenological stages, and further characterize the extracts by HPLC–DAD–ESI/MS. Flower bud extract showed the highest antiproliferative activity as indicated by the lowest GI50 values obtained in all the tested cell lines: MCF-7, breast adenocarcinoma; NCI-H460, non-small cell lung cancer; HeLa, cervical carcinoma; HepG2, hepatocellular carcinoma. Furthermore, porcine liver primary cell culture (PLP2) was used to evaluate toxicity to non-tumor cells. Flavonoids, particularly flavonols and flavones (higher in flower buds) and proanthocyanidins (higher in unripe fruits) were the main classes in the studied samples. Phenolic acids (mainly hydroxycinnamic acid derivatives) were also detected in significant amounts, especially in flower bud extract. Regarding anthocyanins, over ripened fruits gave the highest content. The higher bioactivity observed in flower buds might be related with its higher content in phenolic compounds.